“Evaluación del rendimiento y proteína cruda del pasto Janeiro (Eriochloa polystachya c.v) bajo cinco frecuencias de corte en la zona de Babahoyo” - Bohórquez Galarza, Brayan Jossef (2019)
. SUMMARY The present field experimental work was carried out in the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 ½ of the Babahoyo - Montalvo highway. The zone is of humid tropical climate, according to the classification of Holdribge, with an annual average temperature of 26.2 ºC, an average annual rainfall of 2 656 mm, relative humidity of 76%, vapor tension 27 Mb, dew point 22 ºC and an evaporation of 1 128.8 mm, daily Heliofania of 3.5 HL. The geographic coordinates are west longitude 277 438.26 UTM, south latitude 110 597.97 UTM and altitude of 8 masl. The genetic material used was the pasture Janeiro (Eriochloa polystachya), which was obtained from the livestock sector of the aforementioned Faculty. The objectives that were proposed in the following experimental work were to evaluate the yield and crude protein of the pasture Janeiro under five cutting frequencies; the specific objectives were focused on determining the agronomic performance and crude protein of the pasture Janeiro at the different cutting frequencies in the rainy season; To identify the best cutting season of the pasture in relation to raw protein yield and protein and to perform an economic analysis of the treatments to determine profitability. The treatments studied were the cutting frequencies during the 3, 6, 9, 12 and 15 weeks after the sowing of the Janeiro grass. The experimental design used was of Completely Random Blocks with five treatments and four repetitions. For the comparison and adjustments of means of treatments, the Tukey test will be used at 95% of probabilities. During the present experimental work, agricultural tasks were carried out, such as: soil preparation, division of plots, sowing, irrigation, weed control, fertilization and control of pests and diseases. The evaluated data were plant height, leaf length, green matter production (MV), dry matter production (DM), PB content and economic analysis. Once the results were obtained, it was verified that the plant height data whose highest value was 135.7 cm, the length of the leaf with 25.05 cm, as well as the production values of green and dry matter with 9885.2 and 5974.3 Kg / ha respectively were presented in the cut that was made at 15 weeks after sowing; in the variable of crude protein instead the highest concentration was reached in the cut made at 12 weeks after sowing with 13% and finally the highest net benefit was reported with $ 1181.51 in the yield obtained in the cut executed at 15 weeks after planting. Key Words: yield, cutting, protein, treatments, frecuencies, livestock